(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
In recent years, the activity of the Supreme Court of Justice related to the protection of the federal system introduced as a novelty the consideration of the regions provided for in Article 124 of the Constitution as "contingent political subjects, members of the federal order". This notion was shared by Horacio Rosatti, Juan Carlos Maqueda and Ricardo Lorenzetti in several cases where the autonomous rights of the City of Buenos Aires were debated. The purpose of this paper is to analyze the possible legal consequences of such conceptualization. In particular, its impact on interstate conflicts in relation to the prohibition of entering into political pacts imposed on the provinces, the institutional profile of the regional subject, and its incidence in the scope of the original jurisdiction of the Supreme Court.